Long-Term Adverse Limb Events After Femoral Artery Endovascular Revascularization: The Boston FAROUT Study - Edwin Mandieka, MD; Ramael Ohiomoba, MD, MPH; Piotr Sobieszczyk, MD; Andrew C. Eisenhauer, MD; Thomas Todoran, MD; Scott Kinlay, MBBS, PhD (Journal of the Society for Cardiovascular Angiography & Interventions, 2024)
Background: : Patient, lesion, and procedural characteristics may impact the long-term risks of adverse limb outcomes differently after successful endovascular revascularization for lower extremity peripheral artery disease. The study objective was to assess the relationships of patient, lesion, and procedural characteristics to the subsequent risk of major and minor adverse limb events over the decade after successful endovascular revascularization of the superficial femoral artery for chronic limb-threatening ischemia (CLTI) or lifestyle-limiting claudication. Methods: A retrospective cohort of patients who underwent endovascular revascularization between 2003-2011 were followed for a median of 9.3 (IQR, 6.8-11.1) years. Hazard ratios (HR) and 95% CI from Cox proportional hazards models assessed the risk of major adverse limb events (MALE) (major amputation, bypass, or thrombolysis) or minor revascularization, MALE alone, and minor revascularization alone. Results: There were 232 index limb revascularizations in 185 patients. Longer lesion length was associated with a higher risk of MALE or minor revascularization (HR, 2.09; 95% CI, 1.22-3.60) and minor revascularization alone (HR, 2.53; 95% CI, 1.39-4.61). Current smoking was linked with minor revascularization (HR, 3.83; 95% CI, 1.54-9.56). CLTI was associated with MALE or minor revascularization (HR, 1.89; 95% CI, 1.09-3.29), and MALE alone (HR, 7.43; 95% CI, 3.11-17.79). Black race/ethnicity (HR, 4.74; 95% CI, 1.51-14.9) and low-density lipoprotein >100 mg/dL (HR, 2.76; 95% CI, 1.20-6.35) were linked to MALE alone. Conclusions: Factors related to MALE differed from those related to minor revascularization. Lesion length and smoking were linked to minor revascularization, whereas CLTI, Black race/ethnicity, and elevated low-density lipoprotein were linked to MALE.